Prevalence and influence factors of occupational exposure to blood and body fluids in registered Chinese nurses: a national cross-sectional study - Lihui Zhang; Qi Li; Ling Guan; Lu Fan; Yunxia Li; Zhiyun Zhang; Sue Yuan (BMC, 2022)
Abstract Background Occupational exposure to blood and body fluids poses a threat to medical providers and to nurses especially. This harm is not only physical, but psychology as well and can ultimately impact patient safety. This study aims to understand the prevalence of occupational exposure to blood and body fluids among Chinese registered nurses and explores the factors that influence this exposure. Methods A cross-sectional online survey was conducted for 31 province-level divisions in China, using a self-created questionnaire entitled Status Survey on Occupational Exposure in Nurses. Descriptive statistics were used to describe both the demographic characteristics of the respondents and the characteristics of occupational exposure. Categorical variables were presented as frequencies and percentage, and the relationship between possible influential factors and the occurrence of occupational exposure was determined using binary logistic regression. Results Out of a total of 20,791 nurses analyzed, over half (52.1%) of them had experienced occupational exposure to blood or body fluids, but over 1/3 (34.6%) of them did not ever report their exposures to a supervisor/official. The top three causes of under-reporting were: the source patient failed to test positive for infectious pathogens (43.6%), perception of a burdensome reporting process (24.6%), and indifferent attitude towards being infected (16.9%). Nurses who worked over 8 hours per day had higher risks of exposure (OR 1.199, 95% CI 1.130 to 1.272, P < 0.001, respectively). The occupational exposure risk from providing 1-2 types of PPE is 1.947 times that of providing 9-10 types of PPE (OR 1.947, 95% CI 1.740 to 2.178, P < 0.001). Likewise, the occupational exposure risk of providing 1-2 types of safety-engineered injection devices is 1.275 times of that of providing 5-6 types (OR 1.275, 95% CI 1.179 to 1.379, P < 0.001). Conclusions Occupational exposure to blood and body fluids in registered nurses is common, but the rate of under-reporting such exposure is high. Implementing engineered "sharp" injury prevention devices, following exposure prevention procedures, giving sufficient education and training to healthcare personnel on exposure prevention and control, and developing exposure reporting policies are all steps that can both reduce exposure and increase its reporting.